The log-conformation tensor approach in the finite-volume method framework - Afonso, A. M. (2010)
Made available in DSpace on 2010-04-28T10:07:37Z (GMT). No. of bitstreams: 1 ri57pdf.pdf: 1612383 bytes, checksum: d0bc5a62f20d6d050e2f91660b7b5373 (MD5)